Semiconductor based nanomaterials for harvesting green hydrogen energy under solar light irradiation - Muhammad Bilal, Tahir; Muhammad Faheem, Malik; Adeel, Ahmed; Tasmia, Nawas; Mohsin, Ijaz; Ho, Soon Min; Shabbir, Muhammad; Siddeeg, Saifeldin M. (Taylor and Francis, 2020)
In this review, the evolution of hydrogen in a combined cell system of photoelectrocatalytic and microbial fuel is discussed. Hydrogen is used as chemical fuel and being produced through photoelectrocatalytic method. The semiconductor material was put into the water and irradiated with solar light. After that, the hydrogen is produced by different steps and accumulated. Production of hydrogen also takes place in a microbial fuel cell system. These are electrochemical devices that are initially used to treat the wastewater. But now, this cell has entered into a very interesting field of research which is Bioelectrochemical system (BES). BES produces hydrogen by using biomass as a catalyst and small consumption voltage rather than simple electrolysis of water. The first section explains how hydrogen can be produced individually by these two methods. Then, a comprehensive review is presented on the evolution of hydrogen by combining microbial fuel and photoelectrocatalytic cell system. The continuous production of hydrogen by using (PEC-MFC) hybrid device, sunlight and splitting of water and electro-hydro genesis of microbial cell in fusion device (PEC-MFC) are also reported. This method gives continuous production of hydrogen using wastewater under solar light and also gives the treatment of wastewater. It is a clean energy source and also fulfils today’s demand for energy. At last, a review on the production of hydrogen by the microbial photoelectrochemical system is constructed by photocathode of semiconductor material and an anode of microbial. Production of hydrogen was continuously achieved without external voltage under ultraviolet irradiation.